High rates of organic carbon processing in the hyporheic zone of intermittent streams. Issue 1 (December 2017) - Burrows, Ryan; Rutlidge, Helen; Bond, Nick R.; Eberhard, Stefan M.; Auhl, Alexandra; Andersen, Martin; Valdez, Dominic G.; Kennard, Mark
Abstract Organic carbon cycling is a fundamental process that underpins energy transfer through the biosphere. However, little is known about the rates of particulate organic carbon processing in the hyporheic zone of intermittent streams, which is often the only wetted environment remaining when surface flows cease. We used leaf litter and cotton decomposition assays, as well as rates of microbial respiration, to quantify rates of organic carbon processing in surface and hyporheic environments of intermittent and perennial streams under a range of substrate saturation conditions. Leaf litter processing was 48% greater, and cotton processing 124% greater, in the hyporheic zone compared to surface environments when calculated over multiple substrate saturation conditions. Processing was also greater in more saturated surface environments (i.e. pools). Further, rates of microbial respiration on incubated substrates in the hyporheic zone were similar to, or greater than, rates in surface environments. Our results highlight that intermittent streams are important locations for particulate organic carbon processing and that the hyporheic zone sustains this fundamental process even without surface flow. Not accounting for carbon processing in the hyporheic zone of intermittent streams may lead to an underestimation of its local ecological significance and collective contribution to landscape carbon processes.